Validation of a debiasing addition to Analytical Hieratical Process tools to increase the effects of side-stream utilization and the choice of the filtration system in the European mussel aquaculture and processing industry - Schrøder, Søren Espersen; San Martin, David; Foti, Giuseppe; Gutierrez, Monica; Iñarra Chastagnol, Bruno; Nielsen, J. Rasmus; Larsen, Erling (Frontiers in Food Science and Technology, 2023)
Introduction: New EU regulations for increased sustainability and better utilization of side-streams are pushing the European mussel farming and processing industry to adapt to new regulations regarding their wastewater production, which leads to incentives for optimizing methods for better utilization of this side-stream resource. In this study, one such European company is faced with a choice of a filtration system out of three possible options, to invest in and achieve the option with the best balance between economic gain and environmentally sound production. Method: For this, a specialized Analytical Hieratical Processes (AHP) tool was utilized together with a supplementary Debias Your Decisions (DYD) tool to visualize the local best choice for the company. Results: Based on the generated user weights from the company it was apparent that the user weights were biased towards certain criteria in the AHP tool, which meant that half of the tool’s criteria had greatly diminished influence on the tool’s scores. This brought into question the objectivity of the Performance index (Pi) score results from the AHP tool when the user weights were applied, since these Pi scores deviated significantly from the expert Pi scores. The supplement tool DYD was found to be able to identify the dominant decision biases influencing the user weights in the current case, which enabled the implementation of relevant debiasing techniques to correct for the overweighted user weights from the company. With these corrections and the case company’s input data, the optimum alternative suggested for the case company is membrane filtration based on the final Pi scores for all weight sets. Discussion: This process and final debiased results further validated the AHP tools results as objectively grounded due to their convergence with the experts’ scoring results. This study also served as further validation for the new supplement DYD tool as the current sensitivity analysis showed the tool’s robustness to be high.